Dynamic Crack Analysis in Isotropic/Orthotropic Media via Extended Isogeometric Analysis. (8th April 2014) - Yu, Tiantang; Lai, Yongling; Yin, Shuohui
Abstract : The extended isogeometric analysis (X-IGA) is the combination of the extended finite element method (X-FEM) and the isogeometric analysis (IGA), so the X-IGA possesses the advantages of both methods. In this paper, the X-IGA is extended to investigate the dynamic stress intensity factors of cracked isotropic/orthotropic media under impact loading. For this purpose, a corresponding dynamic X-IGA model is developed, the Newmark time integration scheme is used to achieve a dynamic response, and the dynamic stress intensity factors are evaluated through the contour interaction integral technique. Numerical simulations show that the X-IGA results agree with other available reference solutions, and accurate results can be obtained by using the X-IGA with a relatively coarse mesh.